(untitled) (Педагогіка вищої та середньої школи, 2002)
Author o f the article analyses the formation etymology such as action, operation, reception, skills basing on activity approach. By author’s opinion intellectual skills are the special class in structure of people experience and can’t be interpreted neither as mental nor as thought.